Primary Tuberculosis of the Maxillary Sinus: A case report - Osman, Wail N.; El-Mustafa, Osman M.; Elawad Elsiddig, Mohammed (Gezira Journal of Health Sciences; Vol 7 No 2 (2011), 2011)
Tuberculosis is up-to-date a leading cause of human suffering and loss of life. Although tuberculosis is a systemic disease, primary tuberculosis of the paranasal sinuses is rare. It should be kept in mind in any undiagnosed or atypical clinical infection or inflammation in this region. We present here a case of primary paranasal sinuses tuberculosis in an elderly Sudanese woman. Although Sudan is one of the highest three countries in the incidence of tuberculosis, this is the first case to be reported in Sudan